Controversy Surrounding Indonesia's Program Makan Bergizi Gratis (MBG): Policy Effectiveness and Governance Challenges - Soponyono Soponyono; Usman Idris (CV Edujavare Publishing, 2026)
Program Makan Bergizi Gratis (MBG) has emerged as one of the most ambitious social policies in contemporary Indonesia, attracting widespread public attention due to its scale, fiscal implications, and expected contribution to human capital development. This study examines the controversy surrounding Program Makan Bergizi Gratis (MBG) in Indonesia, focusing on its potential effectiveness and governance challenges. Using a literature review approach, this study synthesizes academic articles, policy reports, and previous studies on school feeding, child nutrition, educational outcomes, and public policy implementation. The findings show that MBG has the potential to improve children’s dietary intake, reduce short-term hunger, increase school attendance, and support learning participation. However, its effectiveness depends on governance quality, including procurement transparency, food safety, budget accountability, institutional coordination, monitoring systems, and local implementation capacity. This study concludes that MBG should be understood as an integrated human development policy rather than a simple food distribution program. Strong governance is essential to ensure that the program produces equitable, sustainable, and measurable benefits for Indonesian children.